Bridging history and special education: Interdisciplinary perspectives on historical thinking and disabilities (Think! Historically: teaching history and the dialogue of disciplines. 5, 2025)
This anthology, based on an international conference held 2023 at the University of Cologne, brings together contributions to the ongoing international discourse on inclusive education and the challenges and potentials of inclusive history teaching. It highlights the need to expand the concept of inclusion beyond a narrow focus on disability. At the same time, it seeks to demonstrate how expertise in special education can enrich the discourses in history education. Aiming to foster interdisciplinary dialogue and mutual learning among researchers and practitioners from different countries and backgrounds, the volume contributes to the theoretical refinement, empirical foundation, and practical development of inclusive approaches to history education.